Comparison of two screening tools for borderline personality disorder (BSL-23 and MSI-BPD) among Indian gay, bisexual, and heterosexual men - Jaiyant Cavale; Dweep Chand Singh; Lata Hemchand (Journal of Men's Health)
Men are underrepresented among those diagnosed with borderline personality disorder (BPD). Paradoxically, gay and bisexual men are overrepresented among BPD-diagnosed individuals. This study compared McLean Screening Instrument for Borderline Personality Disorder (MSI-BPD) and Borderline Symptom List (BSL-23), two popular BPD screening tools, among Indian men, in the context of sexual orientation concealment (SOC) among gay and bisexual men, and dysfunctional behaviors (DBs) and the quality of overall personal state (QOPS) in general. The sample consisted of 45 gay, 43 bisexual and 28 heterosexual men (n = 116) without gender dysphoria aged between 21 and 45. Tools used to evaluate the participants included questions related to sociodemographic variables, MSI-BPD, BSL-23 and the Minority Stress Scale. MSI-BPD and BSL-23 were positively correlated with each other among all the three groups. MSI-BPD was not associated with age, years of education, sexual orientation, or SOC among any of the groups. BSL-23 was negatively correlated with age among gay men. Gay and bisexual men had higher median MSI-BPD scores than heterosexual men, whereas only gay men had a higher median BSL-23 score. Bisexual men had a higher level of SOC than gay men. Education and QOPS were not associated with SOC among gay and bisexual men. Age was positively correlated with SOC among bisexual men, and DBs were negatively correlated with SOC among gay men. There were no differences in DBs or QOPS among the three groups. MSI-BPD is a short and convenient tool to screen men for BPD regardless of their age, education, sexual orientation, or SOC in both clinical and research settings. BSL-23 can be used among men regardless of their sexual orientation as an initial BPD screening tool in clinical settings. Both the tools must be validated among larger samples in India, and translated into regional languages to ensure sociocultural suitability.